Fatty Acid Analysis to Classify Iberian Hams Quality Categories from Different Brands as Affected by the Sampling - Soledad Sánchez; Teresa Antequera; Abraham Pajuelo; Trinidad Perez-Palacios (Journal of Food Quality)
Iberian meat products are classified into four quality categories based on the crossbreeding and feeding of pigs. Meat industries also commonly apply chromatographic analysis to major fatty acids found in the subcutaneous fat taken from the carcass to classify Iberian meat products. Despite the influence of the dry-cured processing, it has not been considered to stablish quality categories of this product, and neither utilizing different lipid sampling methods for analysis. This study evaluated fat from different areas and hams from various brands and quality categories to assess the correspondence between the fatty acid composition from different fat samples, the quality categories of the current classification of Iberian meat products, and the sensory profile of dry-cured hams. The analysed samples included fat from the coccyx in the carcass (CAR), subcutaneous fat from fresh and dry-cured Iberian hams (SCF and SCD, respectively), and intramuscular fat (IMF) from sliced and vacuum-packed dry-cured hams (IMF). These samples were sourced from different brands within each quality category of Iberian products and were evaluated based on their fatty acid composition. Additionally, a quantitative descriptive sensory analysis was conducted on the dry-cured hams in this study. Significant differences in the fatty acid composition and results from the principal component analysis were observed in all four types of analysed samples, indicating similarities among brands from the White and Green quality categories on the one hand and among brands from the Red and Black quality categories on the other hand. Sensory attributes of the dry-cured hams showed minimal significant differences among quality categories, likely due to the high variability among brands. The four types of sampling analysed in this work may be used for quality control in the industries, especially subcutaneous and intramuscular fat from dry-cured Iberian hams, which are easily obtained and handled, and are available until the end of processing.